ksdf.net
ǰλãҳ>>cos(-a)=cos aΪʲô>>

cos(-a)=cos aΪʲô

cos(a+b) =cos(180-c) =-cosC յʽ cos(180-x)= -cosx

ż䣬ſޡ-cosa cos(--a) =cos[-(+a)] =cos(+a) = -cosa

cosУcos sinУsin tanУtan cotУcot sec(-)=-sec csc(-)=csc

cos(a-b)=cosacosb+sinasinbǺȱ任Ĺʽ ɣлл

cos(90+a)-sina ż䣬ſޡ յ90㣬䣻90+ܦʹյʽʱҪǣ90+Ҫڶ޵Ľǣڶ޽ǵֵǸģcos(90+a)-sina. ǸǴģ

ԡ УA+B=-C cos(A+B) =cos(-C) =-cosC ϣﵽ лл

ȽֱϵֱϵxOyλԲOa,b-bʹaĿΪOxԲOڵP1ձ߽ԲOڵP2bʼΪOP2ձ߽ԲOڵP3-bʼΪOP1ձ߽ԲOڵP4ʱP1P2P3P4ֱΪ  P110...

cosab-cosa =-2sin(a+b+a)/2*sin(a+b-a)/2 =-2sin(a+b/2)sin(b/2)

ֱУֱDZa,bбc sinA=a/c cosA=b/c a^2+b^2=c^2 (sinA)^2+(cosA)^2=a^2/c^2+b^2/c^2=(a^2+b^2)/c^2=c^2/c^2=1 (sinA)^2+(cosA)^2=1

վҳ | վͼ
All rights reserved Powered by www.ksdf.net
copyright ©right 2010-2021
磬ַϵͷzhit325@qq.com